Aplicaciones de aeronaves no tripuladas en el control de avance de obras civiles. - Hernández-Moreno, Jorge Alejandro (Instituto Tecnológico de Costa Rica, 2017)
The purpose of this research is to create a methodology that facilitates and speed up the collection of data in order to quantifiably determine the progress of construction work, through the use of drones and commercial Structure from Motion software, so that it could be affordable for small and medium construction companies. The equipment and the software were selected based on a quality / price ratio. A guide was presented, explaining the way of taking data, its process and photogrammetric products (ortomosaics, 3D models, etc.). Finally, the technique proposed in the guide was validated through a real case where the progress of an activity was quantified. In conclusion, if what is going to be measure tolerates precisions up to 1/1000, the technique is applicable. The results of this methodology do not intend to displace conventional methods such as topography, but the manual collection of some data, because it is possible to generate reliable, fast, inexpensive, and accurate metric information. For these reasons, it can be an everyday tool for the construction engineer, with extra gains in job security, accessibility and the possibility of creating visual support material for a better understanding with clients, consultants and field workers.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Drones; Fotogrametría aérea; Control; Monitoreo; Construcción; Software; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture